2014
DOI: 10.1159/000368354
|View full text |Cite
|
Sign up to set email alerts
|

The Compression Anastomotic Ring-Locking Procedure: A Novel Technique for Creating a Sutureless Colonic Anastomosis

Abstract: Background/Aim: Compression anastomoses might represent an improvement over traditional hand-sewn or stapled techniques. Herein, we describe a novel concept of sutureless colonic anastomosis named compression anastomotic ring-locking procedure (CARP). Materials and Methods: The surgical device consists of two anastomotic rings and their associated helping tools, facilitating the placement of the rings into the intestinal ends. Furthermore, four catheters are connected to the surgical device, allowing the evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…Up to now, there is no method for testing the quality of the anastomoses perioperatively and surgeons are left to evaluate colorectal anastomoses by morphological inspection and the use of an air leak test [26]. We have recently reported that the CARP catheter-based system allows quantification of the perioperative compression pressure in the anastomosis of pigs [25], which provides a direct feedback to the surgeon concerning the quality of the anastomosis immediately after its formation. In the present study, we demonstrate that the CARP system was easy to use and efficient in determining the anastomotic compression pressure in patients undergoing elective left-sided colonic resections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, there is no method for testing the quality of the anastomoses perioperatively and surgeons are left to evaluate colorectal anastomoses by morphological inspection and the use of an air leak test [26]. We have recently reported that the CARP catheter-based system allows quantification of the perioperative compression pressure in the anastomosis of pigs [25], which provides a direct feedback to the surgeon concerning the quality of the anastomosis immediately after its formation. In the present study, we demonstrate that the CARP system was easy to use and efficient in determining the anastomotic compression pressure in patients undergoing elective left-sided colonic resections.…”
Section: Discussionmentioning
confidence: 99%
“…Although these devices have been shown to be feasible and safe in numerous studies [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], they do not allow measurement of the quality of the anastomosis perioperatively nor monitoring of the healing process in the anastomosis after surgery. However, the new CARP device (compression anastomotic ringlocking procedure) provides a catheter-based system with access to the healing area within the anastomosis, which allows perioperative measurement of the compression pressure between the intestinal ends within the anastomosis and postoperative monitoring of the anastomotic integrity as documented in a pig model [25]. In that pig study, it was found that CARP was a safe and effective method for colonic anastomoses warranting evaluation in patients undergoing colonic resection.…”
Section: Introductionmentioning
confidence: 99%
“…The C-REX device is a re ned CARP device [27,28] enabling use in minimally invasive surgery as well as transanal construction of a colorectal anastomosis. In brief, the C-REX is a snap-locking device, where the bowel ends are held together by a proximal-and a distal ring.…”
Section: C-rex Devicementioning
confidence: 99%
“…Recently, a novel compression anastomotic device called CARP has been introduced [27]. CARP allows not only a stapel-free anastomosis but has also four built-in catheters enabling measurement of the intraoperative Anastomotic Contact Pressure (ACP) and postoperative monitoring of potential leakage [27,28]. This makes CARP a unique device with capacity to quantify anastomotic integrity.…”
Section: Introductionmentioning
confidence: 99%
“…The methodology is in principal based on a device that locks the two intestinal ends together while the lumen remains open and allows passage of intestinal content. As the anastomosis heals, the short term implant will detach 7–10 days after surgery and follow feces out the natural way [ 11 ].…”
Section: Introductionmentioning
confidence: 99%